Pre-Flood Warning System Based on User Mobility - Mastor, Fateen Atiqah (IRC, 2015)
The occurrence of flood causes millions of Ringgit in damages, along with the loss of life and property, and the devastation of agricultural and livestock. Therefore, an effective pre-flood warning system must be developed to mitigate flood losses and lessen the flood effects. However, when developing a warning system for flood disaster, limited communication during the occurrence of floods and the availability of electricity supplies should be taken into account. Thus, this research project proposes a conceptual framework with three (3) main stages: monitor water level, alert flood victims on flood danger status and inform flood victims to relocate to the nearest relief center. A system architecture has been designed for this research project and a prototype system is developed. The prototype system is made up of a medium sized aquarium tank, a hand pump, HC-SR04 ultrasonic sensor, Arduino UNO R3 and IComsat GSM shield. To validate the proposed prototype system, an experiment with controlled water rising effect is conducted in a lab scale setup. The results prove that the proposed prototype system is reliable as it is able to measure water level accurately and broadcast warning SMS immediately to flood victims. Thus, by having an effective real time pre-flood warning system, immediate action can be carried out in order to save lives and minimize the damages caused by flood disaster.